2019
DOI: 10.21815/jde.019.147
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Meta‐Analysis of the Effect of Interprofessional Education on Health Professions Students’ Attitudes

Abstract: Interprofessional education (IPE) is based on collaborative practices that increase the occasions for communication among those in various health professions. However, there is a paucity of literature about the effectiveness of IPE programs in health professions education. The aim of this systematic review and meta‐analysis was to objectively assess the literature on the effectiveness of IPE in improving health professions students’ attitudes after training. The major scholarly databases were searched for rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
2
24
0
3
Order By: Relevance
“…Interdisciplinary models of scientific research may be more easily translated into community initiatives to enhance health, promote teamwork and collaborative skills and have a significant influence on students’ understanding of collaboration 26,45‐48 . Based on the results in this study, a new model “Dent + X” of research programme, with cooperation between dentistry and other professions, such as engineering, material science and so on, was suggested.…”
Section: Discussionmentioning
confidence: 95%
“…Interdisciplinary models of scientific research may be more easily translated into community initiatives to enhance health, promote teamwork and collaborative skills and have a significant influence on students’ understanding of collaboration 26,45‐48 . Based on the results in this study, a new model “Dent + X” of research programme, with cooperation between dentistry and other professions, such as engineering, material science and so on, was suggested.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies use the ICCAS to evaluate the effectiveness of IPE. The ICCAS measures self‐reported competencies that align with the IPEC Competencies: communication, collaboration, roles and responsibilities, collaborative patient/family‐centered approach, conflict management, and team functioning 24,25 . The didactic‐interactive IPE studies reported in Mazur's clinical case study course, 19 Christian's workshop, 9 and Baker and Durham's course, 17 all demonstrated a significant change from pre‐ to post‐test in all ICCAS competency categories.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of IPE training by Wang et al. reported that the overall effect of IPE training was positive (Z = 6.85, P < 0.01), had a significant influence on students’ understanding of collaboration, and resulted in better attitudes about IP teamwork 24 …”
Section: Introductionmentioning
confidence: 99%
“…The sooner students engage in IPE activities, the more tools they develop to join health teams successfully. Students have been shown to have gained a deeper understanding of the dentist role and the other health workers (Kersbergen et al, 2020) as well as a deeper understanding of collaboration resulting in better attitudes about interprofessional teamwork (Wang et al, 2019). Interprofessional collaborative practice has become widely applied in both public and private sectors as it allows to deliver more effective dental care and better use of resources (Weintraub et al, 2019).…”
Section: Discussionmentioning
confidence: 99%